2020
DOI: 10.1016/j.jsps.2020.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides difficile infections in Saudi Arabia: Where are we standing?

Abstract: Clostridioides difficile infections (CDIs) are infamous healthcare-associated infections for causing watery diarrhea to long-term hospitalized patients with a high mortality rate. Epidemiological reports from western countries showed up-trending pattern in the number of CDIs cases. It is becoming immensely challenging for routine diagnostic protocols to detect CDIs accurately with short turnaround time. In Saudi Arabia, there is a paucity of data about CDIs’ prevalence, recurrence rate, methods of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…A study by Al-Eidan et al [27] also showed that the clinical manifestations of C. difficile infection in most of hospitalized patients included diarrhoea, fever, abdominal pain, and leucocytosis. Basically, CDI diagnosis should depends on stool positive reports as well as clinical symptoms; however, all of the previous studies in Saudi Arabia defined their positive results only upon laboratory investigations of loose stools, without interpreting their findings with patients' clinical symptoms [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study by Al-Eidan et al [27] also showed that the clinical manifestations of C. difficile infection in most of hospitalized patients included diarrhoea, fever, abdominal pain, and leucocytosis. Basically, CDI diagnosis should depends on stool positive reports as well as clinical symptoms; however, all of the previous studies in Saudi Arabia defined their positive results only upon laboratory investigations of loose stools, without interpreting their findings with patients' clinical symptoms [11].…”
Section: Discussionmentioning
confidence: 99%
“…In brief, 25 ml stool sample was added to a tube containing the diluent and conjugate, then transferred to the well of device sample. After 15 min incubation at room temperature, the wash buffer and then the substrate were added to the reaction window [11]. The results interpretation as per manufacturer guidelines.…”
Section: Gdh Antigen And/or Toxins Were Detected Bymentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence rate of CDI among patients with diarrhea in Egypt is 23.6% ( Abu Faddan et al, 2016 ), in Lebanon is 65.2% ( Moukhaiber et al, 2015 ) and in Jordan is 92.4% ( Wadi et al, 2015 ). In Saudi Arabia, there is no published study about prevalence of CDI on a national level, yet, few reports of single-center studies detected low rate of CDIs ( Obaid and Alhifany, 2020 ). One of these studies reported 4.6% prevalence rate of CDI among patients with diarrhea ( Shehabi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%